Rhamnolipids From Pseudomonas aeruginosa Are Elicitors Triggering Brassica napus Protection Against Botrytis cinerea Without Physiological Disorders - Monnier, Noadya; Furlan, Aurélien; Botcazon, Camille; Dahi, Abdellatif; Mongelard, Gaëlle; Cordelier, Sylvain; Clément, Christophe; Dorey, Stéphan; Sarazin, Catherine; Rippa, Sonia (Frontiers in Plant Science, 2018)
Rhamnolipids (RLs) are amphiphilic molecules naturally produced by some bacteria with a large range of biological activities. Although some studies report their potential interest in plant protection, evaluation of their effects and efficiency on annual crops of worldwide agronomic interest is lacking. The main objective of this work was to investigate their elicitor and protective activities on rapeseed crop species while evaluating their physiological effects. Here we report that RLs from Pseudomonas aeruginosa secretome trigger an effective protection of Brassica napus foliar tissues toward the fungus Botrytis cinerea involving the combination of plant defense activation and direct antimicrobial properties. We demonstrated their ability to activate canonical B. napus defense responses including reactive oxygen species production, expression of defense genes, along with callose deposits and stomatal closure as efficient physical protections. In addition, microscopic cell death observations and electrolyte leakage measurements indicated that RLs trigger a hypersensitive response-like defense in this plant. We also showed that foliar spray applications of RLs do not induce deleterious physiological consequences on plant growth or chlorophyll content and that RL protective properties are efficient on several grown cultivars of rapeseed. To our knowledge, this is the first report of RLs as an elicitor that suppresses fungal disease on tissues of an annual crop species under greenhouse conditions. Our results highlight the dual mode of action of these molecules exhibiting plant protection activation and antifungal activities and demonstrate their potential for crop cultures as environmental-friendly biocontrol solution.